Analisis Unsur Manajemen dalam Pengolahan Rekam Medis di Rumah Sakit TNI AU Lanud Roesmin Nurjadin - Ulfa, Henny Maria (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Hospitals must conduct a medical record activities according to Permenkes NO.269 / MENKES / PER / III / 2008 about Medical Record, to achieve the purpose of medical record processing required 5 management elements are: man, money, material, machine, and method. The medical record processing that has been implemented at the Hospital TNI AU LANUD Roesmin Nurjadin that is coding, coding only done for BPJS patients whose conducted by the officer with education background of D3 nursing, it be impacted to the storage part is wrong save and cannot found patient medical record file because are not returned. The purpose of this research is to know the element of management in the processing of medical records at the Hospital TNI AU LANUD Roesmin Nurjadin. This research is done by Qualitative descriptive method, Qualitative approach, instrument of data collection of interview guidance, observation guidance, check list register, and stationery, number of informant 6 people with inductive way data analysis. The result of this research found that Mans elements only amounts to 2 people so that officers work concurrently and have never attended training, material element and machines elements of medical record processing not yet use SIMRS and tracer, while processing method elements follow existing habits and follow the policy of hospital that is POP organization. Keywords: Management elements, medical record processing